QUE PEUT FAIRE L’ABDUCTION DANS LE DIALOGUE PHILOSOPHIQUE ? - FOURNEL, Anda (Studia Universitatis Babeș-Bolyai Philosophia, 2021)
What Abduction Can Do in Philosophical Dialogue? According to Peirce, abduction is a hypothetic-forming process that is necessary to explore unknown areas of knowledge, but also a real scientific method associated with the enquiry. If there is philosophical enquiry, could abduction serve as an appropriate method for such an approach? If so, how can it be used and with a view to what result(s)? We ask whether abduction can bring a potential both for discovery and a logical requirement to the philosophical questioning. In this paper we focus on a philosophy that "is done", in the form of a common enquiry, the "community of philosophical inquiry". The present research explores the advantages and limitations of requiring such a method, in the context of the practice under study.